1996
DOI: 10.1002/jbmr.5650111122
|View full text |Cite
|
Sign up to set email alerts
|

Altered mineral metabolism and bone mass in children during treatment for acute lymphoblastic leukemia

Abstract: Children with acute lymphoblastic leukemia (ALL) often develop bone pain, abnormal gait, and unusual fractures while in remission and receiving continuing chemotherapy. A prospective longitudinal cohort study was undertaken of bone mass and biochemical mineral status in 40 consecutive children (27 male, 13 female, aged 0.3-17.0 years) receiving therapy on the Dana-Farber Cancer Institute protocol 87-01. Radiography, lumbar spine dual-photon absorptiometry, and biochemical measurements of mineral status were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
130
1
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 223 publications
(139 citation statements)
references
References 48 publications
6
130
1
2
Order By: Relevance
“…1 Fractures due to osteoporosis are an important complication of childhood leukemia at diagnosis, as well as during and after ALL therapy. [2][3][4][5][6][7][8][9][10] We recently found that 16% of children with recently diagnosed ALL had vertebral fractures, and that half of the children manifested moderate or severe fractures. Furthermore, each standard deviation (SD) reduction in spine bone mineral density (BMD) Z-score was associated with an 80% increased odds of vertebral fractures.…”
Section: Introductionmentioning
confidence: 99%
“…1 Fractures due to osteoporosis are an important complication of childhood leukemia at diagnosis, as well as during and after ALL therapy. [2][3][4][5][6][7][8][9][10] We recently found that 16% of children with recently diagnosed ALL had vertebral fractures, and that half of the children manifested moderate or severe fractures. Furthermore, each standard deviation (SD) reduction in spine bone mineral density (BMD) Z-score was associated with an 80% increased odds of vertebral fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated abnormalities of BMD and bone mineral metabolism in children with ALL at diagnosis, as well as during and at the completion of chemotherapy [12][13][14][15][16][17][18] . This report highlights the fact that normal bone turnover appears to recover in survivors of ALL, even in those who were exposed to the more intensive chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of bone mineral mass in ALL has been well documented [3][4][5] . However, low bone mineral density (BMD) is only relevant if it persists in the long term so survivors do not achieve a normal peak bone mass by adulthood as seen in healthy populations.…”
Section: Introductionmentioning
confidence: 99%
“…As early as in 1965, a report was published presenting the results of a study on the effects of methotrexate (MTX) treatment on calcium metabolism, demonstrating elevated levels of this element in urine and stool, its lowered levels in blood serum, and indirectly its increased bone resorption [1]. The above data have been reflected in a clinical setting, in patients treated with MTX for acute myeloid leukaemia, where there have been observed pain and difficult uniting of fractures during the course of treatment and remission upon its completion [2][3][4][5][6][7][8]. Although the high doses of steroids have been of significance, the cytostatic agents have been deemed to play an important role here.…”
Section: Chemotherapymentioning
confidence: 99%